Basic Education Public Expenditure Review Phase II : School Based Management in the Philippines, An Empirical Investigation - World Bank (Washington, DC, 2013)
The main objective of this study is to provide a rigorous empirical understanding about the current status of School Based Management (SBM) and the relationship between SBM and learning outcomes in the Philippines with a view to identifying the pathways to improving SBM implementation for improved student achievement. The study makes three potentially important contributions to the policy analysis in support of the implementation of Basic Education Sector Reform Agenda (BESRA) in general and SBM in particular; (i) construction of the Basic Education Information System - National Achievement Test BEIS-NAT Panel Database for 2005-2010; (ii) methodology for policy analysis of SBM; and (iii) Findings from analysis of SBM. These studies have some findings; the findings are grouped into four categories: (a) SBM implementation, (b) resource allocation, (c) principal professional development, and (d) data and information management. Needless to say, these issues are inevitably interrelated so it is important for us to integrate the findings to derive policy implications.